2020
DOI: 10.2478/aut-2019-0049
|View full text |Cite
|
Sign up to set email alerts
|

Review of Printed Fabric Pattern Segmentation Analysis and Application

Abstract: Image processing of digital images is one of the essential categories of image transformation in the theory and practice of digital pattern analysis and computer vision. Automated pattern recognition systems are much needed in the textile industry more importantly when the quality control of products is a significant problem. The printed fabric pattern segmentation procedure is carried out since human interaction proves to be unsatisfactory and costly. Hence, to reduce the cost and wastage of time, automatic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…However, textiles as a unique, heterogeneous, three-dimensional form have their own surface irregularities. Previous research on similar topics has confirmed that the very fundamental mechanisms that determine print quality have not yet been fully elucidated, and the role of textile surface texture has only recently been recognised as one of the fundamental factors in print quality and achieving optimal colour gamut (Park et al 2001;Bae 2007;Collis and Wilson 2012;Kuriki 2015;Parraman 2017;Gooby 2020;Kumah et al 2020). Therefore, any study of the influence of the structural characteristics of the surface of textile materials on print quality, the degree of deformation and spread of droplets on the surface of textile materials, and the penetration of printing ink droplets into the structure of textiles contributes to the understanding of these fundamental mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…However, textiles as a unique, heterogeneous, three-dimensional form have their own surface irregularities. Previous research on similar topics has confirmed that the very fundamental mechanisms that determine print quality have not yet been fully elucidated, and the role of textile surface texture has only recently been recognised as one of the fundamental factors in print quality and achieving optimal colour gamut (Park et al 2001;Bae 2007;Collis and Wilson 2012;Kuriki 2015;Parraman 2017;Gooby 2020;Kumah et al 2020). Therefore, any study of the influence of the structural characteristics of the surface of textile materials on print quality, the degree of deformation and spread of droplets on the surface of textile materials, and the penetration of printing ink droplets into the structure of textiles contributes to the understanding of these fundamental mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…This method has the disadvantage of high labor intensity and poor color measurement stability. 4,5 With the development of spectrophotometry, the spectral imaging and the digital imaging technologies, the fabric color measurement can be realized by electronic equipment, [6][7][8][9] providing an image basis for color segmentation of printed fabric based on machine vision.…”
mentioning
confidence: 99%